2012
DOI: 10.1007/s00442-012-2276-1
|View full text |Cite
|
Sign up to set email alerts
|

Additive and non-additive effects of simulated leaf and inflorescence damage on survival, growth and reproduction of the perennial herb Arabidopsis lyrata

Abstract: Herbivores may damage both leaves and reproductive structures, and although such combined damage may affect plant fitness non-additively, this has received little attention. We conducted a 2-year field experiment with a factorial design to examine the effects of simulated leaf (0, 12.5, 25, or 50% of leaf area removed) and inflorescence damage (0 vs. 50% of inflorescences removed) on survival, growth and reproduction in the perennial herb Arabidopsis lyrata. Leaf and inflorescence damage negatively and indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…First, we observed that the grasshoppers increased proportional leaf damage by 88% if comparing leaf proportional damage in the frog absent, grasshopper present (F−, G+) treatment with the frog absent, grasshopper absent (F−, G−) treatment. We speculate that the increase in leaf damage must have significantly reduced plant photosynthetic capacity and thus the carbon and nutrient sources were limited for seed production (Delaney & Higley 2006;Pellegrino & Musacchio 2006;Puentes & Ågren 2012). Second, we did observe a markedly negative effect of frogs on grasshopper survival.…”
Section: Discussionmentioning
confidence: 50%
“…First, we observed that the grasshoppers increased proportional leaf damage by 88% if comparing leaf proportional damage in the frog absent, grasshopper present (F−, G+) treatment with the frog absent, grasshopper absent (F−, G−) treatment. We speculate that the increase in leaf damage must have significantly reduced plant photosynthetic capacity and thus the carbon and nutrient sources were limited for seed production (Delaney & Higley 2006;Pellegrino & Musacchio 2006;Puentes & Ågren 2012). Second, we did observe a markedly negative effect of frogs on grasshopper survival.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, timing of damage had no significant impact on plant fitness, since pre-flowering and flowering defoliation had similar effects on both growth and reproduction. Negative effects of defoliation on fitness have been reported in other species (Parra-Tabla et al, 2004;Narbona and Dirzo, 2010;Maguire et al, 2011;Irwin and Brody, 2011;Puentes and Ägren, 2012;Zhu et al 2014), where growth and reproduction were reduced as the percentage of defoliation increased.…”
Section: Discussionmentioning
confidence: 81%
“…Parra-Tabla et al (2004) reported that Cnidoscolus aconitifolius (Euphorbiaceae) compensated in leaf growth after herbivory damage, suggesting strong resource allocation to re-establish photosynthetic capacity and increase plant growth and survival. Narbona and Dirzo (2010) Strauss et al, 2001;Narbona and Dirzo, 2010;Irwin and Brody, 2011;Puentes and Ägren, 2012). Our field observations indicated that flower number may increase pollinator visitations since visitors tend to be more abundant in areas with more flowers (Barrios et al, in review).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations